The influence of landscape dis-connectivity on the structure and function of the Krom River, Eastern Cape, South Africa - McNamara, Shaun J (Rhodes University, Faculty of Science, Department of Geography, 2018)
Given that a broad valley and low longitudinal slope are important pre-requisites for wetland formation in dryland environments, it has been proposed that cut-and-fill cycles are largely responsible for the geomorphic evolution of the Krom River valley-bottom wetlands. Research to support this suggestion has focused extensively on the role of phases of incision. As a result, little is known about where sediment mobilised during phases of incision is being deposited (filling phase). This study aimed to address this question to add to the understanding of how cut-and-fill cycles influence the structure and functioning of the Krom River and its wetlands. This was achieved through a reach-scale appraisal of the degree of longitudinal connectivity of the Krom River. The reach used for this appraisal contained an incised section along which the river channel exists as a large gully, and a section immediately downstream of the gully terminus where the Krom River is un-gullied, and flow is diffuse across most of the width of the valley floor. Quantification of the masses of sediment eroded and deposited within the selected reach of the Krom River during a single recent (2012) flood event revealed that the degree of longitudinal connectivity in the Krom River is generally low. During the flood, much of the sediment mobilised by the cutting of the Krom River channel was deposited immediately downstream of the gully terminus, forming a large floodout feature. Particle size analyses of core samples taken along the floodout feature showed that the coarsest fraction of previously mobilised sediment was deposited at the head of the floodout, while finer sediment fractions were deposited progressively further downstream. Field surveys revealed that the pattern of deposition within the floodout feature led to localised steepening of the studied reach of the Krom River downstream of the gully terminus. Surveys of the recently eroded gully revealed that following incision, the eroded stream bed had a lower longitudinal gradient than both the pre-erosional land surface and the regional slope of the Krom River. The results of this study suggest that floodout formation downstream of gullies may promote the transgression of geomorphic thresholds for erosion, such that the development of floodout features leads to likely initiation of new cutting phases in novel locations along the course of the Krom River. They further suggest that the Krom River is capable of intrinsic longitudinal self-recovery through ongoing cut-and-fill cycles. Finally, it would appear that the current cutting phases responsible for the "destruction" of wetlands within the system are part of a cycle that will lead to prolonged geomorphic stability, such that the system is made more suitable for the long-term re-establishment of wetlands.
Keywords: Wetland ecology -- South Africa -- Kromme River (Eastern Cape); Alluvial fans -- South Africa -- Kromme River (Eastern Cape); Sedimentation and deposition -- South Africa -- Kromme River (Eastern Cape); Fluvial geomorphology -- South Africa -- Kromme River (Eastern Cape); Soil erosion -- South Africa -- Kromme River (Eastern Cape)